DAMPAK MANAJEMEN ASET DAN MANAJEMEN UTANG TERHADAP LIKUIDITAS DAN PROFITABILITAS BUMN TERDAFTAR DI BURSA EFEK INDONESIA - Nur Kamiliyah Firizq; Nekky Rahmiyati; Tri Ratnawati (Universitas 17 Agustus 1945 Surabaya, 2019)
The purpose of this study was to determine the impact of asset management and debt management on the liquidity and profitability of SOEs listed on the Indonesia StockExchange for the period 2014-2017. This study use the object of research as 16 BUMNcompanies. The data source used is secondary data, data collection techniques in thisstudy are documentation of company performance reports on the Indonesia StockExchange and company annual reports. The results of the study show that therelationship between asset management and debt management is directly proportional.There is no significant impact of asset management on liquidity and profitability becausethe asset management on 2017 has increased while profitability and liquidity has fallenthis is due to the company's large operational costs financed by debt. Debt managementfor liquidity and profitability has an impact on decreasing liquidity and profitability whendebt management rises. Keywords: Liquidity, Asset Management, Debt Management and Profitability